Dietary Egg Protein Prevents Hyperhomocysteinemia via Upregulation of Hepatic Betaine-Homocysteine S-Methyltransferase Activity in Folate-Restricted Rats. Issue 8 (21st May 2019) - Saande, Cassondra J; Pritchard, Samantha K; Worrall, Deanna M; Snavely, Sarah E; Nass, Caitlyn A; Neuman, Joshua C; Luchtel, Rebecca A; Dobiszewski, Sarah; Miller, Joshua W; Vailati-Riboni, Mario; Loor, Juan J; Schalinske, Kevin L
ABSTRACT: Background: Hyperhomocysteinemia is associated with increased cardiovascular disease risk. Whole eggs contain several nutrients known to affect homocysteine regulation, including sulfur amino acids, choline, and B vitamins. Objective: The aim of this study was to determine the effect of whole eggs and egg components (i.e., egg protein and choline) with respect to 1 ) homocysteine balance and 2 ) the hepatic expression and activity of betaine-homocysteine S -methyltransferase (BHMT) and cystathionine β-synthase (CBS) in a folate-restricted (FR) rat model of hyperhomocysteinemia. Methods: Male Sprague Dawley rats ( n  = 48; 6 wk of age) were randomly assigned to a casein-based diet (C; n  = 12), a casein-based diet supplemented with choline (C + Cho; 1.3%, wt:wt; n  = 12), an egg protein–based diet (EP; n  = 12), or a whole egg–based diet (WE; n  = 12). At week 2, half of the rats in each of the 4 dietary groups were provided an FR (0 g folic acid/kg) diet and half continued on the folate-sufficient (FS; 0.2 g folic acid/kg) diet for an additional 6 wk. All diets contained 20% (wt:wt) total protein. Serum homocysteine was measured by HPLC and BHMT and CBS expression and activity were evaluated using real-time quantitative polymerase chain reaction, Western blot, and enzyme activity. A 2-factor ANOVA was used for statistical comparisons. Results: Rats fed FR-C exhibited a 53% increase in circulating homocysteine concentrations compared with rats fed FS-C ( P  < 0.001). In contrast, serum homocysteine did not differ between rats fed FS-C and FR-EP ( P  = 0.078). Hepatic BHMT activity was increased by 45% and 40% by the EP ( P  < 0.001) and WE ( P  = 0.002) diets compared with the C diets, respectively. Conclusions: Dietary intervention with egg protein prevented elevated circulating homocysteine concentrations in a rat model of hyperhomocysteinemia, due in part to upregulation of hepatic BHMT. These data may support the inclusion of egg protein for dietary recommendations targeting hyperhomocysteinemia prevention.